Mathematics Anxiety and Its Impact on Students’ Learning Outcomes: A Meta-Analysis Review - Faradina, Anggia (Aksioma Education Journal, 2025)
Mathematics anxiety has been widely recognized as a psychological barrier that impairs students' ability to engage with and perform well in mathematics. This study aims to investigate the strength and nature of the relationship between mathematics anxiety and students' academic achievement through a comprehensive meta-analysis of 32 quantitative studies published between 2014 and 2024. The analysis covers data from more than 18,000 students across various educational levels and geographic regions. The results indicate a moderate but consistent negative correlation (r = -0.34) between mathematics anxiety and mathematics achievement, suggesting that higher levels of anxiety are significantly associated with lower academic performance. Subgroup analyses reveal that this effect is stronger in secondary education, among female students, and in countries with exam-oriented educational systems. The study also highlights the importance of using validated instruments to measure anxiety and suggests that cultural and contextual factors play a role in shaping students' emotional responses to mathematics. The findings call for integrated educational strategies that address both cognitive and emotional aspects of learning to improve mathematics outcomes globally.